PEMIKIRAN POLITIK AL-MAWARDI - Amin, Muhammad (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
Western thinkers believe that Muslim scholars were the pioneers of philosophical thought ethics, yet provide no significant contribution in the field of political thought. Furthermore, the former treat the latter as possessing no clear views on political thought and that religion and Islamic civilization have by no means political thought. This point of view is a faulty at all. Since sixteen and seventeenth century Europe failed to acknowledge the characteristics of Muslim political thought. Al-Mawardi was one of the Muslim thinkers who came forward to construct an attractive paradigmatic contribution between social concepts or systems with institutions (state).